Humanitarian Interventions as Practises of Statecraft: Re-Crafting State Sovereignty in Refugee Crises - Soguk, Nevzat (Refuge: Canada’s Journal on Refugees, 1996)
This study argues that humanitarian interventions are not undertaken merely to alleviate the sufferings of people under duress such as refugees. Beyond humanitarianism, they are activities of statist governance-practices of statecraft oriented to re-articulate and re-craft state sovereignty and the hierarchy it signifies, that is, the hierarchy of citizen/nation/state, not only as natural but also as necessary to the peaceful, stable, and secure organization of local and global politics. In as much as humanitarian interventions target refugees as objects of intervention, they appropriate refugees to the task of statecraft; refugees become not only the manifestation of the difficulties for the sovereign state, but also the site of statist practices, which, attendant upon refugees, endeavour continuously to re-articulate the state-centric imagination of life possibilities in local and global interactions. In the process, humanitarianism is typically subordinated to the contingencies of statism in the late 20th Century.